2014
DOI: 10.1182/blood-2014-03-559930
|View full text |Cite
|
Sign up to set email alerts
|

Real world data on primary treatment for mantle cell lymphoma: a Nordic Lymphoma Group observational study

Abstract: • Rituximab and autologous stem cell transplantation are both independently associated with improved overall survival in mantle cell lymphoma.• Male gender is an independent negative prognostic factor in mantle cell lymphoma.There is consensus that young patients with mantle cell lymphoma (MCL) should receive intensive immunochemotherapy regimens, but optimal treatment of elderly patients as well for as patients with limited or indolent disease is not defined. Our aim was to evaluate and compare outcome in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 20 publications
8
128
2
Order By: Relevance
“…Historically, MCL was associated with a dismal outcome, with a median overall survival (OS) of only 3 to 5 years 1,2 ; however, during the past decades, the outcome, especially for younger patients, has improved substantially by an intensified frontline regimen including cytarabine, rituximab, and consolidation with high-dose therapy and autologous stem-cell transplant (ASCT). 1,3,4 Hence, in the recent long-term follow-up of such a regimen, the Nordic MCL2 trial, we observed a median OS and progression-free survival (PFS) of 12.7 and 8.5 years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, MCL was associated with a dismal outcome, with a median overall survival (OS) of only 3 to 5 years 1,2 ; however, during the past decades, the outcome, especially for younger patients, has improved substantially by an intensified frontline regimen including cytarabine, rituximab, and consolidation with high-dose therapy and autologous stem-cell transplant (ASCT). 1,3,4 Hence, in the recent long-term follow-up of such a regimen, the Nordic MCL2 trial, we observed a median OS and progression-free survival (PFS) of 12.7 and 8.5 years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective data suggests that use of radiotherapy with or without chemotherapy engendered significantly better progression-free survival (PFS) at 5 years (73% vs. 13%; p=0.001) with a trend towards overall survival benefit, when compared to patients who did not receive radiation [14]. Radiotherapy as a primary treatment for stage 1-2 MCL patients analyzed retrospectively showed curative results for 3.6% of patients, with 3-year OS of 93% [15].…”
Section: Induction Therapy Stage I and Non-bulky Stage Iimentioning
confidence: 99%
“…These factors likely contribute to the discordance between outcomes described in an optimized clinical trial population, which have improved significantly over the past decade, and real-world outcomes, which remain disappointing. 3 Where is there a role for nonchemotherapy treatment of MCL?…”
Section: Why Is There a Need For Nonchemotherapy Options?mentioning
confidence: 99%
“…11 Nonetheless, the most effective immunochemotherapy regimens are restricted to young, healthy patients who account for ,25% of all patients. 3 Cytotoxic chemotherapy is associated with well-documented toxicities. In addition to usually modest nuisance-type side effects that can sometimes be more significant, such as alopecia, nausea, and fatigue, chemotherapy can cause significant hematological toxicities, resulting in neutropenic fever and other opportunistic infections.…”
Section: Why Is There a Need For Nonchemotherapy Options?mentioning
confidence: 99%
See 1 more Smart Citation